Structural requirements for the functional activity of a U1 snRNA gene enhancer. - Cheung, C H (1993)
The transcriptional enhancer of a chicken U1 small nuclear RNA (snRNA) gene contains a GC-box, an octamer motif, and an SPH motif that are recognized by the transcription factors Sp1, Oct-1, and SBF respectively. Previous work indicated that the octamer and the SPH motifs were both required for U1 gene enhancer activity in frog oocytes when the U1 gene was coinjected with a competing snRNA gene template. Here we show that neither two copies of the octamer motif, nor two copies of the SPH motif, can effectively substitute for the natural combination of octamer and SPH. Furthermore, neither the octamer nor the SPH motif (in the absence of the other) functioned efficiently in combination with a GC-box. Alteration of the spacing between the octamer and SPH motifs also reduced U1 template activity. Several potential cis-acting elements other than the SPH motif, with one possible exception among those tested, were unable to cooperate with the octamer motif to effectively enhance U1 gene expression. These results indicate that rather stringent structural requirements exist with respect to the essential cis-acting motifs present in the U1 enhancer, possibly reflecting the unique properties of the transcription complexes assembled on snRNA gene promoters.